Efficacy and safety of biological agents in adult-onset Still's disease. (July 2015) - Cavalli, G; Franchini, S; Aiello, P; Guglielmi, B; Berti, A; Campochiaro, C; Sabbadini, MG; Baldissera, E; Dagna, L
<x xml:space="preserve">Abstract</x> Objectives: To describe the efficacy and safety of different biological agents in a large cohort of 20 patients with adult-onset Still's disease (AOSD). Method: We retrospectively evaluated 20 patients with severe or refractory AOSD treated with at least one biological agent (anakinra, etanercept, tocilizumab, and adalimumab), followed up for at least 12 months at our Institution. We collected and analysed data on the disease course, treatment outcome, and adverse effects, and compared our data with other published series. Results: The median duration of follow-up was 5 years. In 12 patients a single biological drug induced a clinical response. In eight patients the biological agent that was first administered proved ineffective, and a switch to a different biologic was necessary. In three patients a third biologic was necessary to achieve disease control. The biologics eventually determined a clinical response in all patients. Patients with systemic disease showed better responses than patients with chronic articular disease (p < 0.05). Biological agents allowed either the withdrawal or the tapering of corticosteroid therapy (p < 0.0001) and of disease-modifying anti-rheumatic agents (DMARDs; p < 0.05). Three patients experienced herpes zoster reactivation. Conclusions: This is the longest follow-up of a cohort of AOSD patients treated with biological agents. Our data show that biologics are safe and generally effective in the long-term management of AOSD, particularly in cases with systemic disease, and suggest that a clinical response can be obtained in almost all AOSD patients, although a switch to drugs with a different mechanism of action may be necessary.